A STUDY ON BIOGRAPHY OF THINGS: POSBLOC PUBLIC CREATIVE SPACES - Varidy, Vherendio Novtha; Marwoto, Irmawati (International Review of Humanities Studies, 2024)
This paper discusses the journey of Pasar Baru Post Office using The Biography of Things study in which observes the building from time to time. Pasar Baru Post Office is used as the main source in this paper. Amidst the changes since The Netherland-Colonial era, the building remains still and that became the reason this study was conducted through The Biography of Things study. The research method used in this article is the research framework of Sharer and Ashmore which consists of data collection, processing, and interpretation. The results of the study show that there are some changes in the physical form of the building or its commodification, which can be included as a way to put off the past colonial memory. This can be seen throughout the values and functions shifting that were once used as a place for postal and philatelic services, now the building has become a public creative space.